2017
DOI: 10.1103/physrevb.96.075101
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of type-I and type-II Dirac points in PdTe2 superconductor by external pressure

Abstract: A pair of type-II Dirac cones in PdTe2 was recently predicted by theories and confirmed in experiments, making PdTe2 the first material that processes both superconductivity and type-II Dirac fermions. In this work, we study the evolution of Dirac cones in PdTe2 under hydrostatic pressure by the first-principles calculations. Our results show that the pair of type-II Dirac points disappears at 6.1 GPa. Interestingly, a new pair of type-I Dirac points from the same two bands emerges at 4.7 GPa. Due to the disti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
2
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 72 publications
5
54
2
1
Order By: Relevance
“…Additionally, superconductivity was observed in NiTe 2 under pressure [53] and with the intercalation of Ti into the van der Waals gap (the space between two adjacent chalcogenide layers) [50], and was also predicted in atomically thin systems [54]. Moreover, the energy position of its Dirac node, closer to the Fermi level when compared with similar systems [42,55,56], combined with accessible high-quality single crystals [57][58][59] substantiate the interest on the material.…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…Additionally, superconductivity was observed in NiTe 2 under pressure [53] and with the intercalation of Ti into the van der Waals gap (the space between two adjacent chalcogenide layers) [50], and was also predicted in atomically thin systems [54]. Moreover, the energy position of its Dirac node, closer to the Fermi level when compared with similar systems [42,55,56], combined with accessible high-quality single crystals [57][58][59] substantiate the interest on the material.…”
Section: Introductionsupporting
confidence: 53%
“…While Dirac type-I semimetals exhibit a negative magnetoresistance in all directions [15,17], the transport properties in Dirac type-II semimetals are expected to be anisotropic and present a negative magnetoresistance only in directions where the potential component of the energy spectrum is higher than the kinetic component [38]. PdTe 2 [56] and the family of compounds CaAgBi [91] are the few materials in which the coexistence of Dirac cones of type-I and type-II is expected to occur in the same pair of bands. However, the type-II Dirac node on NiTe 2 is much closer to the Fermi level, and, also, their momentum separation is smaller, providing a better platform to investigate interaction between quasiparticles with different pseudorelativistic signatures.…”
Section: B Dynamically Controlling the Dirac Conementioning
confidence: 99%
“…Stress is also considered to drive topological phase transitions and understand the nature of topological states in PtTe 2 and PdTe 2 . Sun and co‐workers reported that the type‐II and type‐I Dirac points of PdTe 2 can be tuned by external pressure, where the type‐II Dirac points disappears at 6.1 GPa, and the new type‐I Dirac points emerges at 4.7 GPa . Doping is also a direct method to tune the band structure of NTMDs.…”
Section: Structure Of 2d Ntmdsmentioning
confidence: 99%
“…More recently, the transition metal dichalcogenides (TMDs) TMX 2 (TM=Pd, Pt; X=Se, Te) were proposed to host type-II Dirac fermions and were soon verified in angle-resolved photoemission spectroscopy (ARPES) experiments. [17][18][19][20][21][22][23][24][25][26][27][28] Interestingly, PdTe 2 also superconducts below T c =2 K and the Au substitution can boost T c to a maximum value of 4.7 K, making this family of TMDs a promising platform to search for topological superconductors. [29][30][31][32][33][34] However, the Dirac points reported in these materials are located deeply below the Fermi level, with a binding energy of 0.6 eV in PdTe 2 , 0.8 eV in PtTe 2 , and 1.2 eV in PtSe 2 .…”
Section: Introductionmentioning
confidence: 99%